Recovery of arm function during acute to chronic stage of stroke quantified by kinematics - Netha Hussain; Katharina S. Sunnerhagen; Margit Alt Murphy (Medical Journals Sweden, 2021)
Objective: To quantify the longitudinal changes in upper limb kinematics within the first year after stroke and to identify the factors that are associated with these changes. Methods: A total of 66 individuals with stroke from the Stroke Arm Longitudinal Study at the University of Gothenburg (SALGOT) cohort were included if they were able to perform the target-to-target task. Data from a virtual reality haptic target-to-target task at 6 time-points between 3 days and 12 months after stroke were analysed by linear mixed models, while controlling for the impact of cofactors (stroke severity, age, type and side of stroke, sex and presence of diabetes). Results: Kinematic variables of movement time, mean velocity and number of velocity peaks improved over time and were positively associated with younger age, less severe stroke and ischaemic compared with haemorrhagic stroke. Most of the improvement occurred within 4 weeks after stroke, although movement time and number of velocity peaks also improved between 3 and 6 months after stroke. Conclusion: Kinematic variables of movement time, mean velocity and number of velocity peaks were effective in quantifying the longitudinal changes in upper limb kinematics within the first year after stroke.